Committee on Transport Policy and Coordination Indian Railway Policies Before and Since Independence and Some of the Present-day Problems and Railway Rating Policy in Some of the Foreign Countries - Planning Commission (Planning Commission, 1963)
The study analyzes the evolution of Indian Railway policies, both pre- and post-independence, and compares them with international practices in countries such as Germany, France, the United States, Canada, and Argentina. It highlights challenges faced by Indian Railways, including increasing low-margin freight, financial pressures, and competition from road transport. Cost-based rating policies are examined as a means to improve operational efficiency and financial health while addressing social obligations. International experiences show the importance of balancing profitability with equitable service provision. The report emphasizes rationalization of unprofitable passenger services, government subsidies for essential operations, and regular review of transport rate structures. Overall, the study underscores the need for tailored policy adaptations that enhance financial sustainability while aligning with India’s socio-economic priorities.
Committee on Transport Policy and Coordination
Committee on Transport Policy and Coordination
Keywords: Indian Railways; Railway Policies; Cost-Based Rating; Freight Transport; International Comparison; Financial Sustainability; Transportation Regulation; Passenger Services; Government Subsidies; Competition